2022
DOI: 10.1007/s10508-022-02349-w
|View full text |Cite
|
Sign up to set email alerts
|

How Canadian Law Shapes the Health Care Experiences of Women with Female Genital Mutilation/Cutting/Circumcision and Their Providers: A Disjuncture Between Expectation and Actuality

Abstract: This study explored how the reproductive health care experiences of women with female genital mutilation/cutting/circumcision (FGC) were shaped. We used Institutional Ethnography, a sociological approach which allows for the study of social relations and the coordination of health care. From qualitatively interviewing eight women with FGC, we learned that they felt excluded within the Canadian health care system because they were unable to access reconstructive surgery, which was not covered by Ontario’s unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 66 publications
(103 reference statements)
1
4
0
Order By: Relevance
“…The outcome of the rule of law and women's aid in the short and long run conforms with the study of Jacobson et al (2023). The contributing role of women's aid and female wages and salaries in reducing the female genital mutilation prevalence rate are in line with studies by Williams-Breault (2018), Doucet et al (2020), andAmeyaw et al (2021).…”
Section: Cs-ardl Test For Long-and Short-run Estimation Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The outcome of the rule of law and women's aid in the short and long run conforms with the study of Jacobson et al (2023). The contributing role of women's aid and female wages and salaries in reducing the female genital mutilation prevalence rate are in line with studies by Williams-Breault (2018), Doucet et al (2020), andAmeyaw et al (2021).…”
Section: Cs-ardl Test For Long-and Short-run Estimation Resultssupporting
confidence: 85%
“…Likewise, Arendse (2012) emphasises the role of law and government effectiveness in promoting basic education. Jacobson et al (2023) show how law can be used to influence female genital mutilation.…”
Section: Theoretical Framework and Model Specificationmentioning
confidence: 99%
“…Differently, OB/GYNs were expertly trained to read the body according to a very broad range of medical “normal” and to bring the body back to this state. These different readings of women’s bodies are situated in a societal context in which FGC is illegal, in which Canadian laws against FGC have fostered ethical dilemmas for OB/GYNs caring for women with FGC [ 42 ] and in which FGC is stigmatized and more broadly viewed as something that is not “normal” [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Toronto and the GTA, Canada, FGC is stigmatized by a broad societal discourse that opposes FGC (i.e., anti-FGM discourse), resulting in the stigmatization of the practices, women themselves, and related practicing cultures [ 39 ]. In this same context, laws against FGC, which are partial to the cosmetic genital surgeries elected to by Western-born adults, have been found to foster ethical dilemmas for OB/GYNs caring for women with FGC [ 42 ]. Further details about the larger study have been reported [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…By contrast, de-infibulation or clitoral "reconstruction" surgery (including clitoral re-exposition or transposition)-both of which may be interpreted as "undoing FGM"-are often encouraged on that basis even when not strictly necessary to resolve a physical health issue, despite themselves introducing further surgical risk [62][63][64]. Meanwhile, an otherwise similarly-situated woman with a dominant culture background who asks for a medically elective "vaginal rejuvenation" procedure (or even a tellingly named "husband stitch" following childbirth), may be more likely, compared to the Somali woman seeking partial re-infibulation, to find a surgeon willing to "tighten" her vaginal opening or passage (i.e., to suit what her culture regards as an acceptable ideal for female sexual anatomy) [65][66][67][68]. Now consider a Muslim woman from a community that customarily practices what they see as gender-inclusive circumcision: that is, not only male circumcision (partial or total removal of the penile prepuce), but also female circumcision (pricking, nicking, or partial removal of the clitoral prepuce or hood without clitoral glans modification), a common pattern in parts of South and Southeast Asia [69][70][71].…”
Section: Two Types Of Female Genital Modification-or Two Perceivedmentioning
confidence: 99%